The C4 Model Grass Setaria Is a Short Day Plant with Secondary Long Day Genetic Regulation - Doust, Andrew N.; Mauro-Herrera, Margarita; Hodge, John G.; Stromski, Jessica (Frontiers in Plant Science, 2017)
The effect of photoperiod (day:night ratio) on flowering time was investigated in the wild species, Setaria viridis, and in a set of recombinant inbred lines (RILs) derived from a cross between foxtail millet (Setaria italica) and its wild ancestor green foxtail (S. viridis). Photoperiods totaled 24 hours, with three trials of 8:16, 12:12 and 16:8 light:dark hour regimes for the RIL population, and these plus 10:14 and 14:10 for the experiments with S. viridis. The response of S. viridis to light intensity as well as photoperiod was assessed by duplicating photoperiods at two light intensities (300 and 600 mol.m-2.s-1). In general, day lengths longer than 12 hours delayed flowering time, although flowering time was also delayed in shorter day-lengths relative to the 12 hour trial, even when daily flux in high intensity conditions exceeded that of the low intensity 12 hour trial. Cluster analysis showed that the effect of photoperiod on flowering time differed between sets of RILs, with some being almost photoperiod insensitive and others being delayed with respect to the population as a whole in either short (8 or 12 hours light) or long (16 hours light) photoperiods. QTL results reveal a similar picture, with several major QTL colocalizing between the 8 and 12 hour light trials, but with a partially different set of QTL identified in the 16 hour trial. Major candidate genes for these QTL include several members of the PEBP protein family that includes Flowering Locus T (FT) homologs such as OsHd3a, OsRFT1, and ZCN8/12. Thus, Setaria is a short day plant (flowering quickest in short day conditions) whose flowering is delayed by long day lengths in a manner consistent with the short-day response of other members of the grass family. However, the QTL results suggest that flowering time under long day conditions uses additional genetic pathways to those used under short day conditions.